2021
DOI: 10.1088/1757-899x/1144/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Space planning of classroom kindergarten: A case study of KEMAS kindergartens in Batu Pahat, Johor, Malaysia

Abstract: The numbers of kindergarten in Malaysia boost every year as a learning environment for children as preparation for them to face the next level of education in primary school. Thus, comfortable learning environments are essential to enhance not only well-being but also increase the productivity and learning of the children. Therefore, the importance of organization and utilization of spaces can influence children’s activities and learn. This paper aims to identify the criteria of space planning and the issues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, there are kindergarten buildings that were not initially designed for kindergarten purposes and require some alteration to meet the authority's establishment requirements. This may influence the kindergarten's space allocation and congestion [8]. Research conducted by [9] revealed that over 90% of randomly sampled classes (a total of 711 classrooms) were less than 2 m² per person, indicating that these classrooms were unable to accommodate the appropriate number of children as per guidelines.…”
Section: _____________________________mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are kindergarten buildings that were not initially designed for kindergarten purposes and require some alteration to meet the authority's establishment requirements. This may influence the kindergarten's space allocation and congestion [8]. Research conducted by [9] revealed that over 90% of randomly sampled classes (a total of 711 classrooms) were less than 2 m² per person, indicating that these classrooms were unable to accommodate the appropriate number of children as per guidelines.…”
Section: _____________________________mentioning
confidence: 99%
“…Research conducted by [9] revealed that over 90% of randomly sampled classes (a total of 711 classrooms) were less than 2 m² per person, indicating that these classrooms were unable to accommodate the appropriate number of children as per guidelines. In other case studies, inappropriate space allocation such as separating the dining area from the classroom by placing the dining area in the kitchen area, was observed [8]. The inappropriate space allocation contributes to poor indoor air quality (IAQ).…”
Section: _____________________________mentioning
confidence: 99%